Blatisav-1: Un cebo microbiologico contra cucarachas plagas - Milan, O.=700 1 Cueto, N.; Lujan, M.; O'Bourque, E.; Castillo, M.A.; Gainza, E.; Maáo, E.; acosta, N.; Sanchez, M.
(Es, En)
Ilus., 18 ref.
Keywords: BLATTELLA GERMANICA; PERIPLANETA AMERICANA; METARHIZIUM ANISOPLIAE; BACILLUS THURINGIENSIS; BEAUVERIA BAáIANA; CUBA